Informal business empowerment strateg strengthening the weakness aspects of business - Pantja Bambang; Mochamad Yana Aditya; Yatimin Yatimin; Berlianingsih Kusumawati; Adi Musharianto (Institute of Computer Science (IOCS), 2023)
Informal businesses have an important role and contribution to the national economy and development. Although they are also a vulnerable group and can give birth to a new number of poverty. Strategies to strengthen informal business actors need to be carried out so that they continue to develop and become the forerunners of large-scale formal businesses. So they can absorb more labor and reduce poverty. Strengthening informal businesses can be done by identifying the weaknesses experienced and then implementing strategies so that these weaknesses can be avoided. This study aims to analyze the strategies for strengthening informal entrepreneurs with an approach to the aspects of the weaknesses they face. The research was conducted using descriptive-qualitative analysis methods and techniques. The research data consists of primary data (survey using the ghost shopping method and unstructured interviews) and secondary data through literature studies. The results of this study conclude that there are several efforts that need to be made to increase the empowerment of informal businesses, namely through strengthening business capital, utilizing technology, and developing innovation.